2005
DOI: 10.1063/1.2008144
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnet-ferromagnet phase transition in lightly doped manganites

Abstract: Magnetic and structural phase diagrams of the La0.88MnOx, La1−xSrx(Mn1−x/2Nbx/2)O3, Nd1−xCaxMnO3, and Bi1−xCaxMnO3 series, constructed on the basis of x-ray, neutron powder diffraction, Young’s modulus, magnetization and resistivity measurements, are presented. It is shown that the main factor controlling the antiferromagnet-ferromagnet phase transition in the manganites is a type of an orbital state. The results are discussed in the framework of structurally driven magnetic phase separation model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Physical properties of the compounds of stoichiometric cation composition were found to be adjusted by changing the oxygen nonstoichiometry [10]. Self-doped compounds La 0,88 MnO x undergo a sequence of transitions: orbitally ordered antiferromagnetic (x=2.82)ferromagnetic insulator (x=2.9) -ferromagnetic metal (x>2.91) with increasing oxygen content and increasing manganese valence [11]. Due to heterovalent substitution of cations in doped manganites Ln 1-x A x MnO 3±δ (Ln= rare earth element, A = divalent metal cation, δ = oxygen non-stoichiometry), there is a variable oxidation degree of manganese, which is responsible for the appearance of the colossal magnetoresistance and other unique properties of these materials [12].…”
Section: Introductionmentioning
confidence: 99%
“…Physical properties of the compounds of stoichiometric cation composition were found to be adjusted by changing the oxygen nonstoichiometry [10]. Self-doped compounds La 0,88 MnO x undergo a sequence of transitions: orbitally ordered antiferromagnetic (x=2.82)ferromagnetic insulator (x=2.9) -ferromagnetic metal (x>2.91) with increasing oxygen content and increasing manganese valence [11]. Due to heterovalent substitution of cations in doped manganites Ln 1-x A x MnO 3±δ (Ln= rare earth element, A = divalent metal cation, δ = oxygen non-stoichiometry), there is a variable oxidation degree of manganese, which is responsible for the appearance of the colossal magnetoresistance and other unique properties of these materials [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some interesting properties exhibited by these materials include ferromagnetism, 2,3 colossal magnetoresistance, 4,5 half metallicity, 6 orbital ordering, 7,8 the dynamic Jahn–Teller effect, 9 and the polaronic effect 10 . These properties arise from a variety of possible phase states, transitions, and intrinsic correlations of the crystal structure, magnetic characteristics, and transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…The lanthanum manganites have a large number of technological applications, such as in transducers and nonvolatile memory devices and as cathode materials in solid oxide fuel cells 11 . Despite their widespread applications and the numerous studies devoted to these materials, 12 the nature of the interplay between the crystal structure, magnetic properties, and transport properties of manganites is still not entirely understood.…”
Section: Introductionmentioning
confidence: 99%
“…29 and 30)-has an extremely high sensitivity to the variations in oxygen content. 31,32 Its study helps to clarify the general tendencies of the formation of the low-temperature magnetic state in manganites, which is responsible for CMR. Extensive studies of the magnetic properties of manganites by all known methods have demonstrated that the magnetic ordering, which occurs upon cooling, is usually accompanied by the formation of an instability region.…”
mentioning
confidence: 99%